Formação e crescimento do óxido de zinco e óxido de zinco dopado com cobre - Silva, Marlon Nunes da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Zinc oxide (ZnO) nanoparticles were prepared by a sol-gel method, adapted from a synthesis route already well established. The kinetics of the ZnO synthesis was monitored by in situ UV-visible absorbance spectroscopy, pH measurements and small angle X-ray scattering (SAXS). Results allowed proposing a new mechanism of ZnO formation and growth. The second step of this work was to establish a new route of synthesis to obtain copper doped ZnO from two different sources: copper (II) acetate and copper (II) nitrate, at predetermined Zn/Cu ratio (0,1%; 0,25%, 0,5%; 0,75% e 1,0%). These syntheses were also monitored by UV-visible and SAXS spectroscopy. The powders prepared from colloidal suspensions precipitation were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM-EDS). Results show that the synthesis method is suitable for obtaining copper doped ZnO nanoparticles. The wurtzite crystalline structure, characteristic from bulk ZnO, was kept in doped samples. In fact, both the acetate and the nitrate anions inhibit the particles formation and growth, but induce to distinct growth mechanisms: reaction limited cluster-cluster aggregation (RLCA) and diffusion limited cluster-cluster aggregation (DLCA), respectively. Otherwise, the final size of doped particles was kept irrespective of the doping nature and quantity. Qualitative tests of samples response to visible irradiation show photochromic effects, which intensity and time of duration are influenced by the amount of dopant in the sample.
Keywords: Nucleação; Óxido de zinco; Crescimento; Semicondutores - Dopagem; Espectroscopia de raio X